A Pendekatan Pastoral dalam Pendidikan Iman Anak dari Alkitab Menuju Era Digital - YANNI PAEMBONAN; ALFRIDA LEMBANG (Ra'ah: Journal of Pastoral Counseling, 2026)
The aim of this article is to analyze the relevance of pastoral approach in children's faith education in the digital era. The issue addressed is how the church and family can nurture children's faith amidst the challenges of digital technology development, which influences how children learn, interact, and understand spiritual values. The research method used is qualitative with a literature review approach, analyzing various books and journals relevant to the research topic. The findings show that the pastoral approach plays an important role in shaping children's faith through contextual pastoral guidance, open dialogue, and wise utilization of digital media. It also emphasizes that faith education for children should not only focus on doctrinal teaching but also on pastoral relationships that support holistic faith growth. Therefore, the pastoral approach remains relevant in children's faith education in the digital age because it helps the church and family address technological challenges while supporting children's spiritual development comprehensively.